Investigating English Teachers’ Teaching Activities During Covid-19 Pandemic - Malikatul Lutvi; Yudi Basuki (Universitas PGRI Madiun, 2023)
Teaching and learning is an interaction between teachers and students, which is the teacher provides explanations or knowledge to students, while students do something according to the instructions given by the teacher. The research was aimed to find out and describe the English Teachers of Senior High School teaching activities in Trenggalek during the covid-19 pandemic. The research used qualitative focusing on phenomenological research. The research involved the English teachers of Senior High School in Trenggalek as a subject. The research instruments are questionnaires that were analysed using Likert scale and qualitative descriptive way. Research findings show English teacher teaching activities, it shows that English teachers continue to carry out their obligations to teach students during the Covid-19 pandemic, despite the many obstacles they face. They utilize technology-based learning media to support the teaching-learning process during the Covid-19 pandemic. Moreover, given the findings, discussions, and conclusion elaborated above, it is suggested for the government, schools, and next researchers may find benefits of this research.